Effectiveness of Virtual Reality Training for Hand Dexterity in Parkinson’s Subjects: Life Sciences-Physiotherapy - Vaishnavi, G; Saranya, P; Senthil Nathan, C.V; Kamatchi, K; Pavithralotchani, V; Deepa, I; Pradeepa, K; Sumitha, A (International Journal of Life Science and Pharma Research, 2022)
Our aim of the study is to determine the effectiveness of virtual reality training for hand dexterity in Parkinson’s subjects. Parkinson’s disease is one of the most common neurodegenerative disorders. Parkinson’s disease (PD) includes multi level impairments in functional, motor activities which leads to worsening the patient's physical and psychological disabilities, more than 10 million people worldwide are living with Parkinson’s disease. Hand dexterity is as essential as walking ability or postural stabilization or maintaining independence and quality of daily living activities. A comparative study was done with 20 samples. The study was conducted in ACS Medical College and Hospitals, Physiotherapy OP, Krrish Physiotherapy clinic. The duration of treatment was 8 weeks. Both male and female individuals with Parkinson’s disease in concern about hand dexterity difficulty, between the age of 50-55 were included. PD with other neurologic diagnosis, Cognitive impairments, Vision impairments, Uncooperative medication, Cardiac problems, uncooperative were excluded. The outcome measure tools are Box and Block test (BBT) and Chedoke Arm and Hand activities Inventory(CAHAI-13). Based on inclusion and exclusion criteria and outcome measures, 20 subjects were divided into two groups. Group A (10 subjects) were treated with virtual reality training using Leap Motion Controller for 4 days a week for 2 months and Group B (10 subjects) were treated with conventional physiotherapy for 4 days a week for 2 months. On comparing the mean values of Group A& Group B by using CAHAI-13 and BBT score, the Virtual reality Training seems to have shown better results in manual dexterity in Parkinson’s subjects. People with mild to severe disability Parkinson’s have reduced dexterity and problems with hand function